Traditional health practitioner and the scientist: Bridging the gap in contemporary health research in Tanzania - Mbwambo, ZH; Mahunnah, RLA; Kayombo, EJ (Tanzania Journal of Health Research, 2007)
No Abstract. Tanzania Health Research Bulletin Vol. 9(2) 2007: pp.115-120